The Development of the New Monetary Economics - Cowen, Tyler; Kroszner, Randall (Journal of Political Economy, 1987)
This paper looks into the history of economic thought to examine the forerunners of the "new monetary economics." This approach emphasizes the role of regulations on private financial intermediation in determining the particular institutional arrangements that contemporary monetary theory treats as data. The "new view" investigates the possibility that under laissez-faire the unit of account and means of payment, traditionally bundled together in the item called "money," may become separated. The earlier writers who share this perspective have been overlooked by historians of economic thought as well as by recent contributors to the new monetary economics. Many of the insights of these theorists are relevant to modern monetary theory. Copyright 1987 by University of Chicago Press.